2006
DOI: 10.1080/10934520600754136
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Phthalic Acids and Benzoic Acid from Terephthalic Acid Wastewater by Advanced Oxidation Processes

Abstract: Terephthalic acid (TPA) wastewater is traditionally being treated by biological method. This study investigates the degradation of three major toxic target organic species, namely terephthalic acid (TPA), isophthalic acid (IPA), benzoic acid (BA), present in the TPA wastewater, by several advanced oxidation processes. The performance of three main oxidation processes such as photofenton oxidation (UV-H(2)O(2)-Fe), photocatalytic ozonation (UV-O(3)-Fe) and photofenton ozonation (UV-O(3)-H(2)O(2)-Fe) were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Hence, in experiments with those probes only the hydroxylated products are typically measured, while the substrate - often added in excess - is routinely not analyzed for. When detection of these substrates is required, it is usually conducted with far less sensitive UV-based methods [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in experiments with those probes only the hydroxylated products are typically measured, while the substrate - often added in excess - is routinely not analyzed for. When detection of these substrates is required, it is usually conducted with far less sensitive UV-based methods [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radical formation from H 2 O 2 is enhanced in the presence of oxidization agents such as ozone or UV light at 254 nm. The combination of UV light and H 2 O 2 has been applied for several decades for carton decontamination in aseptic packaging (Warriner et al 2000) and also for wastewater treatment (Thiruvenkatachari et al 2006). UV light in combination with H 2 O 2 has been also applied for fresh produce decontamination (Xie et al 2008).…”
Section: Effect Of Physico-chemical Parameters Of Liquid Foodsmentioning
confidence: 99%
“…Thiruvenkatachari et al [10] demonstrated an efficient 80% benzoic acid conversion within 30 min of reaction by homogeneous photo-Fenton systems; additionally, coupling of photo-Fenton oxidation with ozonation led to its complete degradation within 10 min. Andreozzi and Marotta [11] also investigated the activity of Fe 3+ /air/UV (i.e.…”
Section: Introductionmentioning
confidence: 99%